Environmental stress and elicitors enhance taxol production by endophytic strains of Paraconiothyrium variabile and Epicoccum nigrum - Somjaipeng, Supunnika; Medina, Angel; Magan, Naresh (Elsevier, 2016)
This study examined the effect of different elicitors (seven, different concentrations) and environmental factors (water activity (aw), pH) on taxol production by strains of two endophytic fungi, Paraconiothyrium variabile and Epicoccum nigrum, isolated from temperate yew trees. A defined liquid broth medium was modified with elicitors, solute aw depressors at different pH values. For P. variabile, the best elicitor was salicylic acid at 50 mg/l which gave a taxol yield of 14.7 ± 4.8 μg/l. The study of synergistic effects between elicitor, aw and pH on taxol production showed that the highest yield of taxol (68.9 ± 11.9 μg/l) was produced under modified ionic stress of 0.98 aw (KCl) at pH 5 when supplemented with 20 mg/l of salicylic acid. For E. nigrum, serine was the best elicitor which increased yield significantly (29.6 fold) when KCL was used as the aw depressor (0.98 aw) at pH 5.0 with 30 mg/l of serine. The maximum taxol yield produced by E. nigrum was 57.1 ± 11.8 μg/l. Surface response models were used to build contour maps to determine the conditions for maximum and marginal conditions for taxol yield in relation to the best elicitor and aw, and the best pH for the first time. This will be beneficial for identifying key parameters for improvement of taxol yields by endophytic fungi.
Keywords: Elicitors; Water stress; pH; Growth; Taxol production; Enhanced production; Pharma products